Algae-based oral recombinant vaccines - Specht, Elizabeth A.; Mayfield, Stephen P. (Frontiers in Microbiology, 2014)
Recombinant subunit vaccines are some of the safest and most effective vaccines available, but their high cost and the requirement of advanced medical infrastructure for administration make them impractical for many developing world diseases. Plant-based vaccines have shifted that paradigm by paving the way for recombinant vaccine production at agricultural scale using an edible host. However, enthusiasm for “molecular pharming” in food crops has waned in the last decade due to difficulty in developing transgenic crop plants and concerns of contaminating the food supply. Microalgae are poised to become the next candidate in recombinant subunit vaccine production, and they present several advantages over terrestrial crop plant-based platforms including scalable and contained growth, rapid transformation, easily obtained stable cell lines, and consistent transgene expression levels. Algae have been shown to accumulate and properly fold several vaccine antigens, and efforts are underway to create recombinant algal fusion proteins that can enhance antigenicity for effective orally-delivered vaccines. These approaches have the potential to revolutionize the way subunit vaccines are made and delivered – from costly parenteral administration of purified protein, to an inexpensive oral algae tablet with effective mucosal and system immune reactivity.